THE QUALIFICATION IMPROVEMENT OF SOCIAL WORKERS WORKING IN CHILDREN‘S CARE HOMES IN THE CONTEXT OF THEIR RESTRUCTURING - Gudzinskienė, Vida; Raudeliūnaitė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyses the qualification improvement of social workers, who work in children‘s care homes, in the context of their restructuring. A qualitative-empirical study has been conducted by using the method of a semi-structured interview. The study data were processed by using the method of content analysis. The results of the empirical study are based on the experience of 14 social workers, who work in care institutions, which participate in the restructuring, which consists of the changeover from institutional care to the services that are provided to children, who have become destitute of parental care, in a family and community. Internal (an aspiration for a continuous qualification improvement and the desire to share professional experience) and external (changes related to the restructuring, ever higher requirements for social workers, the encouragement and support of the administration of institutions to improve their qualification) stimuli to improve qualification have been highlighted. The most relevant topics of qualification improvement for social workers are the development of personal and social skills in children, the preparation of them for an independent life, the solution of behavioural and psychological problems in children and the preparedness of social workers themselves for the restructuring and the need for supervisions. The topics, which meet their needs, are: the development of social skills, the communication with children and the preparation of them for a family. According to the informants, there is a lack of trainings oriented towards the solution of practical problems which arise while organizing the restructuring. The following problems related to the improvement of qualification were highlighted: the mismatch between the teaching topics and the content, during the trainings for social worker, who work in children‘s care homes, the problems of other social groups, but not of children are analysed. During trainings, there is a lack of the detailed examination of the solution of practical problems. The social workers lack trainings related to the preparation for the restructuring.